Bromine and chlorine chemistry in the Arctic boundary layer - Liao, Jin (Georgia Institute of Technology, 2011)
Halogen chemistry plays an important role in spring time ozone and mercury depletion events (ODEs and MDEs) and may efficiently oxidize hydrocarbons such as the important greenhouse gas methane (CH4) in the polar marine boundary layer. This thesis presents a detailed study of bromine and chlorine chemistry in the Arctic boundary layer based on measurements of bromine and chlorine containing species using chemical ionization mass spectrometry (CIMS). The capability of CIMS to accurately measure bromine oxide (BrO) was demonstrated. The first direct measurements of hypobromous acid (HOBr) were achieved. Conditions that likely favor bromine activation (e.g. high wind speeds) was presented. To advance the understanding of bromine recycling, a time dependent model was built to simulate the bromine speciation. Unexpected high levels of molecular chlorine (Cl2) were observed at Barrow, AK, which had a large impact on methane oxidation and could contribute to ozone loss and mercury oxidation at Barrow, AK. Moreover, BrO levels observed at Summit, Greenland did not explain the under prediction of hydroxyl radical (OH). However, the enhanced OH was found to be coincident with elevated reactive gaseous mercury (RGM). In addition, airborne BrO measurements were found to be generally consistent with airborne observations of soluble bromide based on the response factors of mist chamber to the bromine species and bromine chemical mechanisms. PhD